Pendampingan Pembuatan Sertifikat Halal Bagi UMKM Saladei Ketajen Gedangan Sidoarjo - Mutmainnah, Dewi (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Halal certification provides a sustainable competitive advantage and enhances the business performance of SMEs, both in adherence to halal practices and assurance of halal quality. However, despite increasing awareness of halal certification, the intention to implement it remains relatively low among food and beverage producers. The assistance provided to UMKM Saladei Ketajen Sidoarjo aims to address this issue. The implementation of this Community Service activity was carried out through (1) the planning stage, which included identifying needs and mapping issues, and (2) the execution stage, which involved outreach and assistance, both offline and online. The results of this activity show an increase in awareness and knowledge of halal certification among UMKM Saladei, as well as the successful issuance of the halal certificate in February 2024. Ongoing evaluation is conducted to ensure the sustainability and long-term benefits of the program. In conclusion, this assistance activity has had a positive impact on UMKM Saladei, both in terms of knowledge and business performance. It is recommended to continue similar programs for other SMEs to raise awareness of the importance of halal certification among business owners and the wider community.